An inhibitor of ubiquitin conjugation and aggresome formation1. Issue 9 (10th September 2015) - An, Heeseon; Statsyuk, Alexander V.
<x xml:space="preserve">Abstract</x> An inhibitor of ubiquitin activating E1 enzyme inhibits ubiquitin conjugation and aggresome formation.